2013
DOI: 10.1159/000350101
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Estrogen Receptor a-36 by Breast Cancer Oncogene IKKe Promotes Growth of ER-Negative Breast Cancer Cells

Abstract: Background/Aims: The expression of estrogen receptor-α (ERα) is one of the most important diagnostic and prognostic factors of breast cancer. Recently, ERα-36 has been identified as a novel variant of ER-α. ERα-36 lacks intrinsic transcription activity and mainly mediates non-genomic estrogen signaling. The noncanonical IKK family member IKKε is essential for regulating antiviral signaling pathways and is recently discovered as a breast cancer oncogene. IKKε interacts with and phosphorylates ERα on serine 167,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It has been reported that wtERa functions as a tumor suppressor gene in some cancers including HCC [21]. Though the function of ERa36 in HCC has not yet been defined, it is known to promote the growth of other cancers such as breast cancer cells [27]. The fact that wtERa is reduced in HCC and wtERa functions as a tumor suppressor may well explained the failure of early trial of tamoxifen, as wtER antagonist, to treat HCC [6, 28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that wtERa functions as a tumor suppressor gene in some cancers including HCC [21]. Though the function of ERa36 in HCC has not yet been defined, it is known to promote the growth of other cancers such as breast cancer cells [27]. The fact that wtERa is reduced in HCC and wtERa functions as a tumor suppressor may well explained the failure of early trial of tamoxifen, as wtER antagonist, to treat HCC [6, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative breast cancers (TNBCs) are a heterogeneous set of tumors defined by an absence of actionable therapeutic targets (ER, PR, and HER-2) [36,37]. TNBCs are generally associated with an aggressive clinical course and where targeted therapies are currently limited [38].…”
Section: Discussionmentioning
confidence: 99%
“…[42] The identification of novel molecules that can inhibit IKKε is currently underway as a means to inflammatory processes associated with cancer progression. [47] Moreover, if DADS can reduce IKKε, this could also prevent events downstream to IKKε over expression such as activation of p52 NF-κB dimers [48], [49] estrogen receptor ERα activation, upregulation of cyclin D1 and chemotherapy resistance in breast cancer cells in particular to tamoxifen [50]. In the current study we were focused on IKKi/IKKε because it plays an important role in TNFα signaling.…”
Section: Discussionmentioning
confidence: 99%